2004
DOI: 10.1002/14651858.cd003562.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase 5 inhibitors for pulmonary hypertension

Abstract: Analysis 1.3. Comparison 1 Oral sildenafil versus placebo, Outcome 3 Exercise time on treadmill -1st arm/parallel studies........ Analysis 1.4. Comparison 1 Oral sildenafil versus placebo, Outcome 4 Exercise capacity -6 minute walk test -crossover studies.... Analysis 1.5. Comparison 1 Oral sildenafil versus placebo, Outcome 5 Cardiac index -crossover studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 40 publications
(1 reference statement)
0
5
0
Order By: Relevance
“…This review will also examine the available evidence to determine whether there is any potential benefit or harm in using PDE-5 inhibitors in people with Group 2 to 5 pulmonary hypertension. This review builds on a previous review (Kanthapillai 2004), since which further concepts regarding pathophysiology have been developed, and a number of more recent randomised controlled trials using PDE-5 inhibitors have been published.…”
Section: Why It Is Important To Do This Reviewmentioning
confidence: 99%
“…This review will also examine the available evidence to determine whether there is any potential benefit or harm in using PDE-5 inhibitors in people with Group 2 to 5 pulmonary hypertension. This review builds on a previous review (Kanthapillai 2004), since which further concepts regarding pathophysiology have been developed, and a number of more recent randomised controlled trials using PDE-5 inhibitors have been published.…”
Section: Why It Is Important To Do This Reviewmentioning
confidence: 99%
“…[1] With relation to the pediatric population, there are only case reports that demonstrate possible clinical benefits from the use of sildenafil for PH. [78][79][80][81][82][83][84][85][86][87][88] The largest patient sample used to assess the effects of sildenafil on pediatric patients was reported on by Schulze-Neick et al The sample comprised 24 children with PH secondary to congenital heart disease. This study, controlled with inhaled NO, assessed 12 children by cardiac catheterization and 12 by hemodynamic monitoring during the immediate postoperative period.…”
Section: Digitalis and Diureticsmentioning
confidence: 99%
“…The clinical safety and efficacy of sildenafil in PAH are described in two recent review articles. A systematic review from the Cochrane Collaboration in 2004 reported on the efficacy of sildenafil in 77 subjects with pulmonary hypertension derived from four randomized clinical trials (two acute unblinded studies and two longer-term blinded crossover studies of 2–6 weeks’ duration) ( Kanthapillai et al 2004 ). The authors concluded that the reviewed evidence demonstrated that sildenafil has an acute pulmonary vasodilatation effect and was associated with improvement in symptoms during chronic use.…”
Section: Current Therapy Optionsmentioning
confidence: 99%